Hospital Readiness for Fire Emergency Response in Indonesia: A Literature Study - Nur Chairani Rizki Nasution; FARADILLAH; Abdurrozzaq HASIBUAN (RADINKA JOURNAL OF HEALTH SCIENCE, 2024)
Hospital preparedness for fire response is essential for several critical reasons relating to safety, health and operations. The purpose of the literature review is to find what readiness is needed for hospitals to respond to fire emergencies. In this study, researchers conducted a literature review by examiningvarious journal articles relevant to the research objectives. The results of the literature that have been carried out regarding hospital readiness for fire emergency response are the preparation of fire emergency plans, training and simulations, maintenance of safety equipment, preparation of evacuation routes, budgets, and availability of emergency response teams. Hospital preparedness for fire is very important for the safety of patients, staff and visitors. Things to consider include having a clear emergency plan, regular training for staff, periodic inspection and maintenance of fire-fighting equipment, and efficient evacuation arrangements,Keywords: Fire, Readiness, Hospital, Emergency Response.